Developing Local Content-Based Instructional Graded Reading Materials for Reading Level Three Students - Shella Monica; Machdalena Vianty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This research aimed at analyzing the quality of the newly developed local-content-based instructional graded reading materials for junior high school students in Lubuklinggau. The development of the instructional materials was then analyzed and evaluated in terms of their validity, practicality, and effectiveness using formative evaluation proposed, which consists of self-evaluation, experts review, one-to-one, small group, and field test. The result of expert review showed that the prototype of the product was categorized as having high validity as indicated by the average score of questionnaires on content and construct which was 3.23 (scale 1-4). Moreover, developed instructional reading materials were also considered as highly practical as indicated by the average score of one-to-one evaluation (3.39) and small group evaluation (3.18). Meanwhile, the result of field test evaluation showed that the developed reading comprehension test was highly effective to be used as reading assessment. Meanwhile, the result of field test evaluation shows that developed test could be categorized as effective because there were 20 students (74.07%) out of 27 students in reading comprehension test reached average category which was between 56 and 70. Hence, it was concluded that the developed products, either the test or the teaching materials can become alternative for teaching reading to students whose level of reading is level 3. Keywords: reading assessment; graded reading material; local content-agriculturalproduct